Ambivalensi Penegakan Kode Etik dan Upaya Hukum terhadap Putusan Kode Etik - Siregar, Praise Juinta W.S. (Jurnal Konstitusi & Demokrasi, 2021)
The Election Organizing Honorary Council (hereinafter referred to as DKPP) is a state institution that is authorized by law to enforce the code of ethics. The journey of DKPP in the code of ethics can be said to have dynamics. Follow-up of the DKPP Decision by issuing a Decree issued by the President. The General Election Commission and the Election Supervisory Body are potential legal remedies in the form of a lawsuit to the State Administrative Court. This raises a problem, whether the State Administrative Court does not examine and decide on the lawsuit, considering that the decision is based on the DKPP Decision, which is final and binding, which is final and binding, which can be done if there are parties who are not satisfied with the DKPP Decision.